Primer Design Using Polymerase Chain Reaction for SNPs Analysis in SLC22A1 rs622342 Encoding OCT1 as Metformin Main Transporter - Rochmy Istikharah; Vitarani Dwi Ananda Ningrum; Baiq Maylinda Gemantari (Journal of Pharmacy and Nutrition Sciences, 2018)
Organic Cation Transporter 1 (OCT1) is the primary transporter of metformin mainly located in hepatocytes, which plays an important role in metformin action to inhibit gluconeogenesis so as to reduce blood glucose. Genetic polymorphism of SLC22A1 that encodes OCT1, one of which is rs622342, has been widely reported and proven to decrease the antidiabetic effect of metformin. This study aimed to design primers and to obtain an optimum condition for polymerase chain reaction (PCR) process that can detect the genetic polymorphism of SLC22A1 rs622342. Primers were computationally designed in primer 3 webpage and analyzed with Primer BLAST and Oligo Analyzer. Optimization of PCR condition was conducted for temperatures of denaturation, annealing, and elongation as well as for the number of cycles in PCR process. Sensitivity test was performed on PCR condition using a variety of volumes and DNA template qualities undergoing multiple freeze-thaw cycles. The obtained pair, forward primer (5’- CAG AGA GAA TCA GTG AGC TGT G-3’) and reverse primer (5’- CCC AGG CTG GTC TTT TTA AG-3’), was proven to be capable of amplifying DNA sequence containing SNPs in rs622342 at 96°C denaturation, 60°C annealing, and 72°C elongation temperatures with a 30-cycle iteration. Such PCR condition could amplify DNA with 0.2 µL of template volume and 7 freeze-thaw cycles. Therefore, in addition to the selected primer pairs and PCR condition to analyze SNPs in rs622342, this study also recommends that the volume of DNA template having undergone multiple freeze-thawing be increased if the amplicon PCR products are unqualified.